Micro-crosslinking aqueous binder for lithium ion battery as well as preparation method and application of micro-crosslinking aqueous binder
By developing a micro-crosslinked water-based adhesive for lithium-ion batteries, the problems of low domestic production of positive electrode adhesives in the prior art are solved, high solvent consumption, low adhesion and poor conductivity, and high dispersion, high adhesion and low impedance performance are achieved, and the cycle stability and first-effect performance of the battery are improved, while reducing manufacturing costs and environmental impacts.
Patent Information
- Application Number
- CN202411902759.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-23
- Publication Date
- 2025-03-21
AI Technical Summary
Existing lithium-ion battery positive electrode adhesives such as PVDF have problems such as few domestic products, large solvent consumption, low bonding force, poor electronic and ion conductivity, and it is difficult to meet the needs of lithium-ion batteries in terms of cycle stability, energy density and safety.
A micro-crosslinked water-based binder is developed, containing hydrophilic structural substances, hydrophobic structural substances, crosslinked structural substances, polydispersed structural substances, initiators and deionized water, and the properties of high dispersion, high adhesion and low impedance are achieved through specific preparation methods.
该微交联水系粘结剂对电极活性物质和导电物质具有高分散性和高黏结性,降低了电池的内阻,提高了循环稳定性和首效性能,同时由于使用水作为分散介质,制造成本降低且更为环保。
Smart Images

Figure CN119662165A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of electrode binders, in particular to a slightly cross-linked aqueous binder for lithium ion batteries and a preparation method and application thereof. Background Art
[0002] In recent years, lithium-ion batteries have been closely related to our lives. They have shown broad application prospects and market value in large energy storage systems ranging from portable electronic devices to electric vehicles. Today's lithium-ion batteries are developing in the direction of extended cycle stability, high energy density, high transmission rate capability, low cost and safety. In lithium-ion batteries, binders are an important inactive material. They account for a small proportion, but play an important role. They play a bonding role between active materials, conductive agents and current collectors, stabilize the CEI film, and make them have overall connectivity, thereby reducing the ion transmission resistance of the electrode, while making the electrode have good mechanical properties and processing properties to meet the needs of industrial production.
[0003] At present, the binder used in the positive electrode of lithium-ion batteries is polyvinylidene fluoride (PVDF). There are two problems with the use of PVDF: ① PVDF used in lithium-ion batteries is mainly imported, with little domestic production; ② PVDF needs to be dissolved in N-methylpyrrolidone, which causes a large amount of solvent evaporation, consumes a lot of costs, and there are certain risks in using solvents. ③ The adhesion of PVDF to active substances is mainly generated by van der Waals forces, and its adhesion is relatively low, and the battery capacity is easy to decay. ④ PVDF has poor electronic and ionic conductivity, and the internal resistance of the prepared battery is large.
[0004] In addition, SBR water-based binders contain unsaturated double bonds, and when used as positive electrode adhesives, there is a risk of oxidation during charging. Therefore, in order to address the above problems, it is necessary to develop a more environmentally friendly, low-priced, and better battery electrochemical performance positive electrode binder for lithium-ion batteries. Summary of the invention
[0005] In order to address the deficiencies in the prior art, the present invention provides a micro-cross-linked aqueous binder for lithium-ion batteries, a preparation method and application thereof, which has high dispersibility, high adhesion, high initial efficiency, low impedance and high rate performance for electrode active materials and conductive materials, thereby ultimately improving the quality of the manufactured battery.
[0006] To achieve the above-mentioned purpose, the present invention provides the following technical solution: a slightly cross-linked aqueous binder for lithium-ion batteries, comprising the following raw materials, a hydrophilic structure material, a hydrophobic structure material, a cross-linked structure material, a polydisperse structure material, an initiator and deionized water.
[0007] Preferably, the hydrophilic structural substance is at least one of acrylic acid, itaconic acid, starch paste, hydroxyethyl acrylate, allyloxy isomeric alcohol ether sulfate ammonium salt, allyloxy hydroxypropyl sulfonate sodium, acrylamide, and an olefinic monomer containing a polyethylene glycol segment.
[0008] Preferably, the hydrophobic structure substance is at least one of acrylonitrile, ethyl acrylate, butyl acrylate, cyclohexyl acrylate, isononyl acrylate, lauryl acrylate, ureido methacrylate, and tetrahydrofurfuryl acrylate.
[0009] Preferably, the cross-linked structure substance is at least one of glycidyl methacrylate, allyl acrylate, polyethylene glycol diacrylate, N,N-methylenebisacrylamide, triethylene glycol dimethacrylate, and pentaerythritol triacrylate.
[0010] Preferably, the polydisperse structure substance is at least one of tert-butyl acrylate, tert-butyl maleate, ditert-butyl isocyanurate glyceryl, and tert-butyl epoxy acrylate.
[0011] Preferably, the initiator is sodium persulfate.
[0012] The present invention also provides a method for preparing a slightly cross-linked aqueous binder for a lithium ion battery, comprising the following steps:
[0013] S1. Weigh deionized water, polydisperse structure materials, hydrophilic structure materials, and some hydrophobic structure materials into a reactor and stir them thoroughly;
[0014] S2. During the stirring process, nitrogen is introduced into the reactor to remove oxygen, the temperature is gradually raised to 50-90°C, and part of the initiator is added, and the reaction is carried out for 2-6 hours;
[0015] S3, adding the remaining hydrophobic structure material and the remaining initiator dropwise into the reactor, and reacting at 65-85° C. for 1-5 hours;
[0016] S4. After the reaction is completed, add an alkaline solution into the reactor to adjust the pH of the system to 6.0-7.5, thereby obtaining a slightly cross-linked water-based adhesive.
[0017] Preferably, the alkaline solution is at least one of Li2CO3 and LiOH.
[0018] The present invention provides a micro-crosslinked aqueous binder for lithium ion batteries and a preparation method and application thereof, which have the following beneficial effects compared with the prior art:
[0019] The micro-cross-linked aqueous binder in the present invention has high dispersibility for electrode active materials and conductive materials, which is beneficial to the uniform dispersion of active materials and conductive agents, and effectively improves the coating effect of electrode slurry; at the same time, it has high adhesion, low impedance, and cycle stability, which can ensure the structural stability of the positive electrode material, and uses water as the dispersion medium, which is safer and more environmentally friendly during the drying process, thereby reducing the manufacturing cost of the battery.
[0020] The slightly cross-linked aqueous binder in the present invention is rich in polar groups, has excellent adhesion to active materials and conductive agents, can ensure the structural integrity of electrode materials, and contains certain cross-linked structures and flexible segments, which can buffer the stress generated by the volume change of active materials.
[0021] The micro-crosslinked aqueous binder of the present invention contains lithium supplementing materials, which can improve the initial efficiency of lithium-ion batteries.
[0022] The flexible segments in the polymer segments of the slightly cross-linked aqueous binder of the present invention give the polymer a high resilience effect, which can resist the stress generated by the volume change of the active material, thereby ultimately improving the quality of the manufactured battery. BRIEF DESCRIPTION OF THE DRAWINGS
[0023] The drawings described herein are used to provide a further understanding of the present application and constitute a part of the present application. The illustrative embodiments of the present application and their descriptions are used to explain the present application and do not constitute an improper limitation on the present application. In the drawings:
[0024] Figure 1 This is the infrared spectrum of the slightly cross-linked water-based adhesive in Examples 1-4 of the present invention;
[0025] Figure 2 Impedance spectra of Examples 1-3 of the present invention and the comparative example;
[0026] Figure 3 The 0.5C charge and discharge cycle curves of the batteries of Example 3 of the present invention and the comparative example;
[0027] Figure 4 The 1C battery charge and discharge cycle curves of Examples 4-5 of the present invention and the comparative example are shown. DETAILED DESCRIPTION
[0028] The following implementation rules are used to explain in detail the implementation methods of this application, so that the implementation process of how this application uses technical means to solve technical problems and achieve technical effects can be fully understood and implemented accordingly.
[0029] Example 1
[0030] A method for preparing a slightly cross-linked aqueous binder for lithium-ion batteries is as follows:
[0031] Add 240g of deionized water, 41g of acrylic acid, 1.0g of allyloxy isomeric alcohol ether sulfate ammonium salt (SR-10), 4g of acrylamide, 20g of acrylonitrile, 17g of ethyl acrylate, 0.03g of triethylene glycol dimethacrylate, 10g of tetrahydrofurfuryl methacrylate, and 2.5g of versatile maleate into a reactor and stir well; introduce nitrogen into the reaction system, then gradually raise the temperature to 75°C, and add 0.8g of sodium persulfate; after reacting for 2h, mix 4g of ethyl acrylate and 4g of tetrahydrofurfuryl methacrylate evenly, dissolve 0.16g of sodium persulfate in 20g of deionized water, and dropwise add it into the reaction system within 30min for polymerization, and after the addition is completed, heat it to 80°C and keep it for reaction for 1h; then drop Li2CO3 solution into the reactor to adjust the pH to 7, and a slightly cross-linked aqueous adhesive can be obtained.
[0032] Example 2
[0033] A method for preparing a slightly cross-linked aqueous binder for lithium-ion batteries is as follows:
[0034] Add 360g of deionized water, 62g of methacrylic acid, 1.5g of COPS-1 (sodium allyloxyhydroxypropyl sulfonate), 36g of acrylonitrile, 43.5g of ethyl acrylate, 0.04g of N,N-methylenebisacrylamide, and 6g of tert-butyl epoxy acrylate into the reactor and stir well. Pass nitrogen into the reaction system, then gradually heat up to 65°C, add 0.9g of sodium persulfate, and react for 2h. Then, dissolve 9g of ureido methacrylate and 0.18g of sodium persulfate in 10g of deionized water, and drop them into the reaction system within 60min for polymerization. After the addition is completed, heat to 75°C and keep warm for 5h. Then drop LiOH solution into the reactor to adjust the pH to 7 to obtain a slightly cross-linked water-based adhesive.
[0035] Example 3
[0036] A method for preparing a slightly cross-linked aqueous binder for lithium-ion batteries is as follows:
[0037] Add 150g of deionized water, 20g of acrylic acid, 0.5g of ammonium salt of allyloxy isomeric alcohol ether sulfate (SR-10), 12g of acrylonitrile, 12.5g of ethyl acrylate, 0.015g of allyl acrylate, 1g of tert-butyl epoxy acrylate, and 4g of acrylamide into the reactor and stir well; introduce nitrogen into the reaction system, then gradually heat up to 70°C, add 0.3g of sodium persulfate, and react for 3h. Then, dissolve 2g of ureido methacrylate and 0.06g of sodium persulfate in 10g of deionized water, and drop them into the reaction system within 60min for polymerization. After the addition is completed, heat to 80°C and keep warm for 2h. Then, drop LiOH solution into the reactor to adjust the pH to 7 to obtain a slightly cross-linked water-based adhesive.
[0038] Example 4
[0039] A method for preparing a slightly cross-linked aqueous binder for lithium ion batteries, based on Example 3, using 12.5 g of isononyl acrylate instead of ethyl acrylate, and the rest is the same as Example 3.
[0040] Example 5
[0041] A method for preparing a slightly cross-linked aqueous binder for lithium-ion batteries, based on Example 3, using 7g of tetrahydrofurfuryl methacrylate to replace 4g of acrylamide and 3g of ethyl acrylate; and dropping NaOH and LiOH solutions to adjust the pH to 7, thereby obtaining a slightly cross-linked aqueous binder.
[0042] Comparative Example
[0043] When commercially available PVDF is used to make batteries, N-methylpyrrolidone is used as a solvent, and the rest of the proportions are the same as those in the embodiments of the present invention. According to the mass ratio of lithium iron phosphate: conductive carbon black: carbon nanotubes: PVDF = 94.5:2:0.5:3 (mass ratio), N-methylpyrrolidone is added as a solvent, and the solid content of the slurry is adjusted to 45%. It is added to a mortar and ground and blended for 30 minutes. The resulting slurry is coated on aluminum foil using a 100μm wet film preparation device, and the aluminum foil is placed in an 80°C oven to dry for 12 hours, and then placed in a 110°C oven to dry for 6 hours. Test the peel strength of the slurry on aluminum foil. At the same time, it is then sliced into battery electrode sheets and assembled into CR2032 button batteries in a glove box.
[0044] Quality Inspection
[0045] The swelling rate and dissolution rate of the aqueous binder in Examples 1-5 and the comparative example to the electrolyte, the peel strength and the electrochemical performance were tested.
[0046] 1. Swelling rate and dissolution loss rate test
[0047] Weigh a certain weight of the prepared micro-crosslinked water-based adhesive, evenly place it on a polytetrafluoroethylene plate, and then bake it at 60°C for about 48 hours to obtain a polymer film. Take a 1×1cm polymer film and weigh its weight as m0; place it in an electrolyte solution at 60°C for 48 hours; after taking it out of the electrolyte, wipe off the solution on the surface and weigh it as m1; then dry the taken polymer film at 120°C to constant weight, and measure its weight as m2. The calculation formula is as follows:
[0048]
[0049] The specific results are shown in the following table.
[0050] Table 1 Swelling rate and dissolution rate
[0051] category Swelling rate, % Dissolution rate, % Example 1 7.65±0.82 0.84±0.25 Example 2 0.93±0.26 3.82±0.92 Example 3 0.31±0.05 4.28±0.49 Example 4 1.95±1.39 3.51±1.17 Example 5 2.56±1.30 2.53±1.13 Comparative Example 32.68±5.23 2.60±3.30
[0052] It can be seen from Table 1 that the swelling degrees and swelling rates of Examples 1-5 are all lower than those of the comparative example, indicating that the micro-crosslinked structure can slow down the swelling of the binder polymer in the electrolyte, which is beneficial to maintaining the integrity of the electrode.
[0053] 2. Peel strength and electrochemical performance test
[0054] Take the corresponding aqueous binder to prepare the lithium iron phosphate positive electrode. According to the mass ratio of lithium iron phosphate: conductive carbon black: carbon nanotube: binder = 94.5:2:0.5:3 (mass ratio), add it into a mortar and grind and blend it for 30 minutes. The battery slurry is prepared into a 45% solid content. The obtained slurry is coated on aluminum foil using a 100μm wet film preparation device. The aluminum foil is placed in an 80℃ oven and dried for 12h, and then placed in a 110℃ oven and dried for 6h. Test the peel strength of the slurry on the aluminum foil. At the same time, take a part of the coated electrode and assemble it into a CR2032 button battery in a glove box.
[0055] The electrochemical impedance spectroscopy (EIS) of the test battery, the voltage is the open circuit voltage, the frequency range is 1MHz-0.1Hz, and the voltage amplitude is 5mV. After activation, the charge and discharge test is carried out on the LANHE CT2001A blue battery test system at 0.5C and 1C rates, the charge and discharge voltage range is 0.01-1.5V, and the test is carried out at room temperature. Test parameters such as first charge capacity, coulomb efficiency, and rate charge and discharge.
[0056] The corresponding results are shown in Table 2.
[0057] Table 2 Peel strength and impedance
[0058] category Peel strength, N / m Button cell battery impedance, Ω Example 1 164.33 283 Example 2 149.33 230 Example 3 129.16 394 Example 4 143.82 295 Example 5 135.67 328 Comparative Example 8.67 623
[0059] From the above table, we can know that the prepared micro-crosslinked water-based binder has a good binder for lithium iron phosphate active material, and its peel strength is significantly higher than that of the traditional PVDF system. Figure 2 The impedance of button batteries is lower than that of traditional PVDF batteries. The main reason is that the prepared micro-cross-linked aqueous binder contains a dispersed structure that can effectively disperse the conductive agent and reduce the impedance of the battery.
[0060] from Figure 3 and Figure 4 It can be seen that the cycle performance of the embodiment of the present invention is better than that of the traditional PVDF (comparative example) adhesive in the 1C rate charge and discharge, and the cycle performance is also better than that of the comparative example PVDF adhesive series in the 0.5C rate charge and discharge, indicating that the water-based binder with a micro-cross-linked structure can effectively improve the cycle performance of the battery, and no solvent is added, which is more environmentally friendly.
[0061] Although embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the appended claims and their equivalents.
Claims
1. A slightly cross-linked aqueous binder for lithium-ion batteries, characterized in that: The invention comprises the following raw materials: a hydrophilic structure material, a hydrophobic structure material, a cross-linked structure material, a polydisperse structure material, an initiator and deionized water.
2. The slightly cross-linked aqueous binder for lithium ion batteries according to claim 1, characterized in that: The hydrophilic structure substance is at least one of acrylic acid, itaconic acid, starch paste, hydroxyethyl acrylate, allyloxy isomeric alcohol ether sulfate ammonium salt, allyloxy hydroxypropyl sulfonate sodium, acrylamide, and olefinic monomers containing polyethylene glycol segments.
3. The slightly cross-linked aqueous binder for lithium ion batteries according to claim 1, characterized in that: The hydrophobic structure substance is at least one of acrylonitrile, ethyl acrylate, butyl acrylate, cyclohexyl acrylate, isononyl acrylate, lauryl acrylate, ureido methacrylate and tetrahydrofurfuryl acrylate.
4. The slightly cross-linked aqueous binder for lithium ion batteries according to claim 1, characterized in that: The cross-linked structure substance is at least one of glycidyl methacrylate, allyl acrylate, polyethylene glycol diacrylate, N,N-methylenebisacrylamide, triethylene glycol dimethacrylate, and pentaerythritol triacrylate.
5. The slightly cross-linked aqueous binder for lithium ion batteries according to claim 1, characterized in that: The polydisperse structure material is at least one of tert-butyl acrylate, tert-butyl maleate, ditert-butyl isocyanurate glyceryl, and tert-butyl epoxy acrylate.
6. The slightly cross-linked aqueous binder for lithium ion batteries according to claim 1, characterized in that: The initiator is sodium persulfate.
7. A method for preparing a slightly cross-linked aqueous binder for lithium ion batteries according to any one of claims 1 to 6, characterized in that: The following steps are involved: S1. Weigh deionized water, polydisperse structure materials, hydrophilic structure materials, and some hydrophobic structure materials into a reactor and stir them thoroughly; S2. During the stirring process, nitrogen is introduced into the reactor to remove oxygen, the temperature is gradually raised to 50-90°C, and part of the initiator is added, and the reaction is carried out for 2-6 hours; S3, adding the remaining hydrophobic structure material and the remaining initiator dropwise into the reactor, and reacting at 65-85° C. for 1-5 hours; S4. After the reaction is completed, add an alkaline solution into the reactor to adjust the pH of the system to 6.0-7.5, thereby obtaining a slightly cross-linked water-based adhesive.
8. The method for preparing a slightly cross-linked aqueous binder for lithium ion batteries according to claim 7, characterized in that: The alkaline solution is at least one of Li2CO3 and LiOH.
9. Use of the slightly cross-linked aqueous binder as claimed in claims 1-6 or the slightly cross-linked aqueous binder prepared by the preparation method as claimed in claims 7-8 on the positive electrode of a lithium iron phosphate battery.